Documents about the forced resignation of Imre Szabó, reformed deacon, pastor of the budapest-fasor congregation in 1951 - Vezsenyi, Péter (Church History Review, 2022)
Imre Szabó (1891–1955) was the first deacon of the Reformed Presbytery of Budapest and pastor of the Budapest Fasor Reformed Congregation for more than twenty-eight years, serving the Gospel faithfully throughout the upheavals of the first half of the twentieth century and the tragic turns in his own life. His oeuvre left a lasting mark on the 20th century history of Hungarian Reformed Christianity, but church history writing has so far failed to thoroughly explore and evaluate his pastoral and church-organizing ministry.